Data processing procedure using distribution of slopes of phase differences for broadband VHF interferometer. Issue 10 (28th May 2014) - Akita, Manabu; Stock, Michael; Kawasaki, Zen; Krehbiel, Paul; Rison, William; Stanley, Mark
Abstract The upgraded VHF digital interferometer (VHF DITF) system is introduced which can continuously sample the radiation associated with lightning. A new processing technique was implemented which uses the distribution of slopes of the phase difference versus frequency to locate the radiation source. By using this technique, frequency components which are not due to lightning can be excluded and low as well as high amplitude sources are located. As a result, both positive breakdown and negative breakdown are located, and negative recoil leaders (recoil leaders) are visualized in great detail. The recoil leaders which continue into the positive charge region are seen to slow their propagation and dim their radiation as they cross the flash initiation region. Analysis of the relative received power of the different breakdown types, negative leaders, recoil leaders, and positive leaders, also can be made. In both the intracloud and cloud‐to‐ground flash, the modes of the distributions of received power for negative leaders, recoil leaders, and positive leaders were approximately the same. The brightest emissions seen from the positive leader were substantially lower than the brightest emission seen from the negative leader. The results also indicate that positive leaders as well as lower elevation negative leader emit more low frequency radiation than recoil leaders and high‐elevation negative leaders. By continuously sampling the VHF waveform, the upgraded VHF DITF locates many weak sources which the previous system was not capable of locating.